Combining Clinical Parameters and Acute Tubular Injury Grading Is Superior in Predicting the Prognosis of Deceased-Donor Kidney Transplantation: A 7-Year Observational Study - Wang, Jiali; Liu, Jinqi; Wu, Wenrui; Yang, Shicong; Liu, Longshan; Fu, Qian; Li, Jun; Chen, Xutao; Deng, Ronghai; Wu, Chenglin; Long, Sizhe; Zhang, Wujun; et al. (Frontiers in Immunology, 2022)
Background: We developed a pragmatic dichotomous grading criterion to stratify the acute tubular injury (ATI) of deceased donor kidney. We intended to verify the predictive value of this criterion for the prognosis of deceased kidney transplantation. Methods: The allografts with ATI were classified into severe and mild group. Severe ATI was defined as the presence of extreme and diffuse flattening of the tubular epithelial cells, or denudement of tubular basement membrane. Clinical delayed graft function (DGF) risk index was calculated based on a regression model for post-transplant DGF using 17 clinical parameters related to donor-recipient characteristics. Results: 140 recipients were enrolled: 18 severe and 122 mild ATI. Compared with mild ATI, severe ATI had more donors after cardiac death, higher median donor terminal serum creatinine level (dScr), and longer median cold ischemia time. Severe ATI had a higher DGF rate (55.6% vs 14.6%, P < 0.001), longer DGF recovery time (49.6 vs 26.3 days, P < 0.001), and a lower eGFR at 1 month (23.5 vs 54.0 mL/min/1.73 m2, P < 0.001), 3 months (40.4 vs 59.0, P = 0.001) and 6 months after transplant (46.8 vs 60.3, P = 0.033). However, there was no significant difference in eGFR at 1-year or beyond, graft and patient survival. The predictive value of combined dScr with ATI severity for DGF rate and DGF recovery time was superior to that of dScr alone. The predictive value of combined DGF risk index with ATI severity for DGF was also better than that of DGF risk index alone; however, the association of DGF risk index with DGF recovery time was not identified. Chronic lesions including glomerulosclerosis, interstitial fibrosis, arterial intimal fibrosis and arteriolar hyalinosis were associated with declined post-transplant 1-year eGFR. Conclusion: Based on our pragmatic dichotomous grading criterion for ATI in pre-implantation biopsy, donor kidney with severe ATI increased DGF risk, prolonged DGF recovery, decreased short-term graft function, but demonstrated favorable long-term graft function. Our grading method can offer additive valuable information for assessing donor kidney with acute kidney injury and may act as an effective supplementary indice of Banff criteria.